Environmental remediation through various composite membranes moieties: Performances and thermomechanical properties. (December 2022) - Khurram, Abdul Rehman; Rafiq, Sikander; Tariq, Alisha; Jamil, Asif; Iqbal, Tanveer; Mahmood, Hamayoun; Mehdi, Muhammad Shozab; Abdulrahman, Aymn; Ali, Abulhassan; Akhtar, Muhammad Saeed; Asif, Saira
Abstract: Pollution harms ecosystems and poses a serious threat to human health around the world through direct or indirect effects on air, water, and land. The importance of remediating effluents is paramount to reducing environmental concerns. CO2 emissions are removed efficiently and efficaciously with mixed matrix membranes (MMMs), which are viable replacements for less efficient and costly membranes. In the field of membrane technology, MMMs are advancing rapidly due to their good separation properties. The selection of filler to be incorporated in mixed matrix membranes is very considered very important. There has been considerable interest in MOFs, carbon nanotubes (CNTs), ionic liquids (ILs), carbon molecular sieves (CMSs), sulfonated fillers (SFs), and layered silicates (LSs) as inorganic fillers for improving the properties of mixed matrix membranes. These fillers promise superb results and long durability for mixed matrix membranes based on them. The purpose of this review is to review different fillers used in MMMs for improving separation properties, limitations, and thermomechanical properties for environmental control and remediation. Graphical abstract: Image 1 Highlights: Discussion on the nature of inorganic fillers and their interactions with polymeric matrix. Critical review on gas separation performance of mixed matrix membranes (MMMs) by incorporation inorganic fillers. Discussion on the effects of Inorganic fillers on the thermomechanical properties of MMMs.